MFD (Monetary and Financial Systems Department) Technical Assistance to Recent Post-Conflict Countries. (Policy Papers; Policy Paper, 2004)
This paper reviews the recent experience with technical assistance (TA) to postconflict economies in the monetary and financial areas with a view to providing lessons for ongoing and future work.